2002
DOI: 10.1007/s00213-001-0953-6
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine potentiation of brain stimulation reward reversed by DHβE and SCH 23390, but not by eticlopride, LY 314582 or MPEP in rats

Abstract: These results indicate that nicotinic and dopamine D(1) receptors are involved in the nicotine-induced potentiation of brain stimulation reward, while actions at dopamine D(2), mGlu(2/3) and mGlu(5) receptors did not modulate this effect of nicotine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
151
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(170 citation statements)
references
References 54 publications
16
151
3
Order By: Relevance
“…Given the fidelity of the concurrent access model for dissociating the two reinforcement-related effects of nicotine, this paradigm may be considered a useful preclinical screen for potential smoking cessation aides. Arguably, negative allosteric modulators of mGluR5 represent potential therapeutics that do not interfere with nicotine's ability to enhance mood (ie decrease ICSS threshold, Harrison et al, 2002) or to enhance cognitive function (ie reinforcement enhancing effects, present studies). A treatment that could reduce nicotine seeking without altering the mood-or cognitive-enhancing effects of nicotine (eg MTEP) could be an effective adjunct to current replacement therapies.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Given the fidelity of the concurrent access model for dissociating the two reinforcement-related effects of nicotine, this paradigm may be considered a useful preclinical screen for potential smoking cessation aides. Arguably, negative allosteric modulators of mGluR5 represent potential therapeutics that do not interfere with nicotine's ability to enhance mood (ie decrease ICSS threshold, Harrison et al, 2002) or to enhance cognitive function (ie reinforcement enhancing effects, present studies). A treatment that could reduce nicotine seeking without altering the mood-or cognitive-enhancing effects of nicotine (eg MTEP) could be an effective adjunct to current replacement therapies.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies by Markou and colleagues (Harrison et al, 2002;Paterson and Markou, 2005;Paterson et al, 2003) suggest that the mGluR5 system may mediate primary reinforcement by nicotine, without impinging upon the reinforcement enhancing effects of drug administration. For example, administration of a selective antagonist, 2-methyl-6-(phenylethynyl)-pyridine (MPEP), decreased nicotine self-administration in rats and mice and decreased the motivation to take nicotine as measured on a progressive ratio schedule (Paterson and Markou, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine conditioned place preference (CPP), nicotine self-administration, and intracranial self-stimulation (ICSS) have been used to investigate the rewarding and reinforcing effects of nicotine. DHβE blocked nicotine CPP, nicotine self-administration, and nicotine enhancement of ICSS (Corrigall, Coen, & Adamson, 1994;Grottick et al, 2000;Harrison, Gasparini, & Markou, 2002;Kenny & Markou, 2006;Walters, Brown, Changeux, Martin, & Damaj, 2006). In contrast, the α7 nAChR antagonist MLA had no effect on nicotine CPP or nicotine self-administration (Grottick et al, 2000;Walters et al, 2006but see Markou & Paterson, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have demonstrated that bupropion altered nicotineassociated changes in reward, nicotine self-administration, nicotine withdrawal-associated conditioned place aversion, and somatic signs of withdrawal. Acute nicotine enhanced brain reward functioning as measured by intercranial self-administration (ICSS), whereas withdrawal from chronic nicotine produced a decrease in brain reward functioning (EppingJordan et al, 1998; Harrison et al, 2002;Skjei and Markou, 2003). Cryan and colleagues (2003) reported that a low dose of bupropion blocked the acute nicotine enhancement of ICSS and also reversed the decrease in ICSS when rats were withdrawn from chronic nicotine.…”
Section: Introductionmentioning
confidence: 99%